MONITORING KUALITAS PH DAN KEKERUHAN AIR LAUT DALAM MENJAGA EKOSISTEM TERUMBU KARANG MENGGUNAKAN METODE FUZZY LOGIC - Asrori, Hazynatul; EP, Amak Yunus; Muhammad Priyono Tri Sulistyanto (Jurnal Fakultas Teknologi Informasi, 2024)
The condition of the sea and coastal areas is getting worse every day. Poor sea conditions will damage the marine ecosystem because the quality of sea water is a very important factor for the survival of coral reefs and other marine biota. To reduce the impacts that occur due to poor water quality, a monitoring and control system is needed so that water quality can be controlled properly. Therefore, the author makes a coral reef ecosystem monitoring system using the Fuzzy Logic method, the system will monitor the pH and turbidity of water, then use fuzzy as a decision support method to determine the quality of sea water.